POLA PEMBINAAN ANAK BERMASALAH DALAM PERSPEKTIFPEKERJAAN SOSIAL DAN KOMUNIKASI (STUDI EVALUASI DI LEMBAGA PEMBINAAN KHUSUS ANAK “LPKA” KELAS II AMBON) - Josephus Noya; Demsy Wattimena (BADATI, 2022)
The Institute for Special Guidance for Children is a special prison that only fosters child prisoners. The purpose of this research is to evaluate the implementation of patterned coaching in institutions.This study used a qualitative method by taking location in LPKA Class II Ambon. The data sources are child prisoners as informants and guidance officers. Data collection methods and tools used in this study were interviews using interview guides and documentation. The data analysis method is a qualitative data analysis technique. The results showed that the pattern of guidance in LPKA, namely, spiritual coaching, legal awareness coaching, attitude & character development, physical health coaching, and skills coaching, are all routinely implemented three times a week supported by three advisors and also facilitated with coaching infrastructure. . From the results of this study, suggestions are given to prison students to be more diligent in following coaching and for the prison authorities are expected to further improve the quality of coaching, add development facilities and infrastructure, and also bring in child psychologist coaches.